Fascinating : the life of Leonard Nimoy - Michelson, Richard (Alfred A. Knopf, 2016)
Presents a portrait of the late actor best known as Spock from "Star Trek," including his early dreams of becoming an entertainer and the ways his character reflected his experiences of being different.